1968
DOI: 10.1097/00006254-196805000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Histologic and Chromosomal Abnormalities in Cervical Neoplasia

Abstract: T h e chromosome patterns of 124 cases of cervical intraepithelial neoplasia (dysplasia and carcinoma in situ) and 87 cases of invasive carcinoma of the cervix were examined with the direct squash technique. Diploid or near diploid modes occurred exclusively in the dysplasias. Heteroploidy occurred in both carcinoma in situ and invasive carcinoma but the majority of cases of carcinoma in situ exhibited near tetraploid modes whereas the majority of invasive carcinomas had modes in the near diploid range. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Stained sections from each biopsy were analyzed for the presence of features associated with classical HPV infection (condyloma) and with CIN. The former include epithelial maturation and nuclear atypia in the surface epithelial cells (koilocytotic atypia); the latter include nuclear atypia in all layers of the epithelium and the presence of abnormal mitoses as previously described (4,12,20). Nuclear atypia is defined as hyperchromatism, pleomorphism, anisonucleosis, and coarse chromatin distribution.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Stained sections from each biopsy were analyzed for the presence of features associated with classical HPV infection (condyloma) and with CIN. The former include epithelial maturation and nuclear atypia in the surface epithelial cells (koilocytotic atypia); the latter include nuclear atypia in all layers of the epithelium and the presence of abnormal mitoses as previously described (4,12,20). Nuclear atypia is defined as hyperchromatism, pleomorphism, anisonucleosis, and coarse chromatin distribution.…”
Section: Resultsmentioning
confidence: 94%
“…We have previously shown that HPV 16 is present in a unique subset of condylomata which contain abnormal mitoses (5). Abnormal mitoses classically are associated with squamous neoplasms, including carcinomas in situ (12). Results of these studies (5,7) indicate that HPV 16 is associated with different types of precancerous lesions that have certain morphological features in common.…”
mentioning
confidence: 97%
“…Because we demonstrated resistance to both these phenomena in the erythroplakia cultures, we be- Table 1. lieve that this phenotype is an early event in the pathogenesis of SCC-HN and that it contributes to the suprabasal proliferation of dysplastic oral lesions, including erythroplakia [28]. Two senescent carcinoma cultures, BlCR 66 and BlCR 80, and the erythroplakia culture BlCR E5 also possessed numerical chromosome aberrations, which are often associated with progression towards SCC [39]. We have not formally shown that the keratinocytes from BlCR 37, BlCR 66, and BlCR 80 are actually invasive, but because BlCR 37 was isolated from a lymph-node metastasis, we can be confident that this culture is carcinoma derived.…”
Section: Discussionmentioning
confidence: 99%
“…The tetraploid state is lost in 1-2 years, consistent with transient tetraploid cells that lose chromosomes at high frequency . Similarly, during the evolution of cervical, breast, and bladder cancer, there is evidence for wholegenome duplication followed by chromosome losses (Dutrillaux et al 1991;Kirkland et al 1967;Olaharski et al 2006;Ottesen 2003;Shackney et al 1995a,b). Tetraploidization also occurs in hyperplastic lesions of the pancreas (Tanaka et al 1984), in localized prostate cancer (Deitch et al 1993, Montgomery et al 1990, Pihan et al 2001, and some colon adenomas (Hamada et al 1988, Levine et al 1991.…”
Section: Figurementioning
confidence: 99%